2011
DOI: 10.1179/1743281211y.0000000004
|View full text |Cite
|
Sign up to set email alerts
|

Modelling magnetohydrodynamic processes in DC arc steelmaking furnace with bottom electrodes

Abstract: The electrovortex movement of liquid metal in a direct current arc furnace with a bottom electrode under its own electromagnetic field has been investigated. The physical and mathematical formulations of the processes are given. The algorithm of a solution was developed and the method and software packages for modelling the processes were chosen. The results of electromagnetic and magnetohydrodynamic field analyses in the industrial furnace are given. The verification of results has been done by comparing them… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 7 publications
1
11
0
Order By: Relevance
“…The comparison of the obtained results by different software packages and methods showed an insignificant difference of ,3%. [11][12][13][14][15] The similarity of the calculations performed by different methods and software packages confirms the reliability of the methods and significance of the results.…”
Section: Verification Of Obtained Resultssupporting
confidence: 59%
“…The comparison of the obtained results by different software packages and methods showed an insignificant difference of ,3%. [11][12][13][14][15] The similarity of the calculations performed by different methods and software packages confirms the reliability of the methods and significance of the results.…”
Section: Verification Of Obtained Resultssupporting
confidence: 59%
“…A column of liquid metal of high velocity is formed between the two electrodes, reaching values close to 50 cm s −1 at the bottom electrode and about 10–20 cm s −1 below the top electrode, drastically decreasing away from this column with values about 5 cm s −1 . [ 37 ] Overall, thermal stratification is less than 50 °C. Zhao et al [ 38 ] reported also similar values, in the order of 30 °C for an EAF of 60 ton with a current of 20 kA and a bottom electrode with a radius of 0.7 m. Ramirez et al [ 39 ] reported that increasing the arc length increased the heat input but decreased the velocity of the liquid, for example, increasing the arc length from 15 to 35 cm decreased the maximum velocity from 1.5 to 1 m s −1 .…”
Section: Driving Forces For the Motion Of Liquid Steel In A Conventio...mentioning
confidence: 99%
“…At present, high-power arc steel-making furnaces with melt bath capacity exceeding 100 tons and installed power exceeding 100 MVA with currents of 50-150 kA in the electrodes [1,2] may be referred to as a separate group among electrometallurgical units. Such furnaces are most commonly made as multiple-electrode ones to reduce loads on the electrodes and distribution of the input electric power [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…An urgent task for furnaces with a large volume of metal is the effective mixing of the melt, which contributes to the intensification of heat transfer as well as its temperature and chemical homogenization. Along with the use of melt mixing by purging with various gases, electromagnetic mixing methods based on various magnetohydrodynamic effects are currently used [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation